PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF Tricalysia chevalieri K. KRAUSE LEAVES EXTRACT - ABBA, H.M,; ABUBAKAR, U. A, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
An assessment of phytochemical composition and antimicrobial activity of methanol leaf extract of Tricalysia chevalieri was evaluated for the presence of phytochemicals. The bacterial pathogens used were subjected to biochemical tests for proper identification and antibacterial susceptibility of the crude extracts against clinical isolates of Escherichia coli and Klebsiella pneumoneae were determined at varying concentrations 200mg/ml 100mg/ml 50mg/ml 25mg/ml using agar well diffusion method. The MIC and MBC of the crude extracts were also determined. The result of Phytochemical screening revealed the presence of Saponins, Tannins, Steroids, Glycosides, Phenols and Flavonoids in the crude extracts. The methanol leaf extract exhibited good activity against the test organisms. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the leaf extract ranges from 50- 100mg/ml for Escherichia coli and Klebsiella pneumoneae 25-200mg/ml respectively. The extract showed significant inhibition against all the test organisms.hence bactericidal in its effects. This study concludes that the methanol leaf extract of Tricalysia chevalieri contains bioactive components that have broad spectrum antimicrobial properties that can be used as a good source of drugs to cure Dysentery and Pneumonia.